Gratitude, Mindfulness, and Sleep Quality in University Students - Shahid, Laiba; Khan, Muhammad Luqman; Iqbal, Muhammad Maqsood (Regional Lens, 2025)
The aim of this research is to explore the relationship between gratitude, mindfulness, and sleep quality. High levels of stress are common in university students, which has an impact on their general health and sleep quality. In order to understand how psychological elements, lead to improved sleep. The study explores whether practicing gratitude and mindfulness improves sleep quality by lowering stress and promoting emotional control. A correlation design was used to gain data in this study. The study collected data from a sample of 250 university students using a convenient sampling technique. Gratitude Questionnaire, Mindfulness Attention Awareness Scale, and Sleep Quality Scale were used for data collection. The relationship was investigated using a statistical technique including correlation, multiple regression, and Haye's process model. Significant positive associations between gratitude, mindfulness, and sleep quality were found via statistical analysis. Research findings indicate that students who scored higher on gratitude and mindfulness had better sleep satisfaction and reduced sleep disruption. To better understand this relationship future research should investigate intervention-based study and longitudinal impact.